O blog como meio de comunicação: origem, apropriações e horizontes da blogosfera na sociedade contemporânea - Marques, Márcia Siqueira Costa (2012)
This research project focuses on a study of the origins, nature, social importance, reception scheme, cultural dynamics and scope of blogs. In this context, the blog will be considered as the primary means of communication of the emerging era of cyberculture. The project examines the role of this new media and this universe of blogs and bloggers the blogosphere as a new means of political resistance to the information monopoly of major international media groups. Fundamentally, it seeks to understand the dynamics of this new relationship and its economic and cultural appropriation. This objective, in particular, contextualizes the research question: How are blogs are situated in this new communication scenario? And further, what role does this new means of production, circulation and exchange of information play vis-à-vis mass media? The research problem includes questions concerning the motivational factors underlying the blogging experience, aiming to determine if blogs are indeed the main media of this new generation; if they are actually opposed to traditional media or simply update them in a different way; their functional models; and their social and economic appropriation. The working hypotheses are as follows: the social relevance of blogs obfuscates the importance of the traditional means of communication, prevailing as a means to obstruct the hegemony of the large media conglomerates; cyberspace promotes new categories of communication and culture and modifies categories of analysis of the communication process; due to its specificity and underlying proposal, the cyclical and structural characteristics of the bloggers universe may render the general theory of communications outdated in many respects. The theoretical framework of this research is based on the epistemology of cybercultural dromocracy, especially with regard to the concepts of glocal and glocalization proposed by Trivinho (2007); Castells s (2003, 2006, 2009) concepts of networks, flows and mass self-communication; La Boétie s (2009) idea of voluntary servitude; and Searle s (2002) concept of intentionality. The methodology encompasses a bibliographic review based on the most recent national and international publications on the subject, as well as on magazine and newspaper articles, specific websites and blogs, while the corpus of analysis is composed of the Brazilian blogosphere, its readers/producers and their interrelationships. With these elements, the research aims to discover and grasp what lies behind the act of blogging and of reading blogs. The collected and summarized data will serve as the basis for a comparison of the various aspects of blogs and for an analysis of the blogosphere culture, in order to test the validity of the aforementioned hypotheses